Simultaneous Estimation and Validation of Atorvastatin Calcium and Aspirin in Combined Capsule Dosage Form by RP HPLC Method - B. V. Suma; K. Kannan; V. Madhavan; Chandini R. Nayar (E-Journal of Chemistry)
A new simple, specific, precise and accurate revere phase liquid chromatography method has been developed for estimation of atorvastatin calcium (AST) and ASPIRIN (ASP) simultaneously in a combined capsule dosage forms. The chromatographic separation was achieved on a 5 – micron C 18 column (250x 4.6mm) using a mobile phase consisting of a mixture of Acetonitrile: Ammonium Acetate buffer 0.02M (68:32) pH 4.5. The flow rate was maintained at 0.8 ml/min. The detection of the constituents was done using UV detector at 245 nm for AST and ASP. The retention time of AST and ASP were found be 4.5915 ± 0.0031 min and 3.282 ±0.0024 min respectively. The developed method was validated for accuracy, linearity, precision, limit of detection (LOD) and limit of quantification (LOQ) and robustness as per the ICH guidelines.